Gender- and Age-Specific Associations between Visceral Obesity and Renal Function Impairment - Tsao, Yu-Chung; Chen, Jau-Yuan; Yeh, Wei-Chung; Li, Wen-Cheng (Obesity facts, 2019)
Objective: Although obesity is associated with an increased risk of chronic kidney disease, this trend becomes nonsignificant following adjustment for cardiovascular risk factors. The present study aims to investigate whether visceral obesity is independently associated with renal function impairment. Method: The medical records of 14,529 male and 10,561 female Chinese adults undergoing health check-ups during 2013–2015 were retrospectively collected. The baseline characteristics, including the degree of visceral fat and the percentage of body fat, were compared. The association between study groups and renal function impairment was investigated using regression models adjusted for confounding factors. Results: All variables differed significantly among non-obese, peripheral, and central type obese subjects, both younger and older, and of both genders, except for hsCRP in older male subjects (p = 0.053) and eGFR in older female subjects (p = 0.098). Unadjusted univariate analysis showed that central obesity contributed significantly to renal function impairment in all age groups and in both genders. After adjusting for possible confounding factors, only central obesity was found to be an independent factor of renal function impairment in all groups, except for men under 45 years of age. Conclusion: Visceral obesity is independently associated with renal function impairment in all ages and both genders, except for males younger than 45 years.